Facing the forest entrepreneurs - Healy, Hazel (New Internationalist, 2013)
Communities are scrambling to protect their lands from the tree plantations multiplying across Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra

‘Operation of the Market's Study. How the poor access, hold and trade land: Findings from research in two settlements in Tete, Mozambique - Gordon, Ross; Taljaard, Reathe; Massuanganhe, Egildo, Egildo (Progressus Research Development Consultancy, 2013)
The way in which informal land transactions occur and the extent to which they result in tenure security and asset creation in these informal settlements is not well understood. For this reason this study comprises research into two informal settlements (namely Matundo and Mateus Sansão Muthemba [Sansão Muthemba]) in Tete, Mozambique, so as to understand how the poor access, hold and trade land. This research forms part of a larger research programme being undertaken by Urban LandMark which includes similar studies in Lilongwe (Malawi), Maputo (Mozambique), Luanda (Angola) and Durban, Cape Town and Johannesburg (South Africa). Reports on these other research projects can be seen on www.urbanlandmark.co.za.
Keywords: DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; governance / governação; land governance / gestão de terra